2015
DOI: 10.1039/c5em00252d
|View full text |Cite
|
Sign up to set email alerts
|

A first look at the influence of anthropogenic climate change on the future delivery of fluvial sediment to the Ganges–Brahmaputra–Meghna delta

Abstract: We employ a climate-driven hydrological water balance and sediment transport model (HydroTrend) to simulate future climate-driven sediment loads flowing into the Ganges-Brahmaputra-Meghna (GBM) mega-delta. The model was parameterised using high-quality topographic data and forced with daily temperature and precipitation data obtained from downscaled Regional Climate Model (RCM) simulations for the period 1971-2100. Three perturbed RCM model runs were selected to quantify the potential range of future climate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 46 publications
8
43
0
Order By: Relevance
“…Furthermore, our results are comparable to estimates by Darby et al (2015) who reported increases of 52-60 % in total sediment load for the end of the century compared to 1981-2000. Their estimates were derived from precipitation and temperature data downscaled from several Regional Climate Model simulations for the SRES A1B.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Furthermore, our results are comparable to estimates by Darby et al (2015) who reported increases of 52-60 % in total sediment load for the end of the century compared to 1981-2000. Their estimates were derived from precipitation and temperature data downscaled from several Regional Climate Model simulations for the SRES A1B.…”
Section: Discussionsupporting
confidence: 88%
“…Below follows a synthesis of present state parameter values (of parameters 1-6 in Table 1A (Islam et al 1999;Darby et al 2015;Ray et al 2015;Prasch et al 2015). 2.…”
Section: Synthesis Of Reported Parameter Values: Present Statementioning
confidence: 99%
See 3 more Smart Citations